PSAK 57: COMPREHENSIVE ASSESSMENT OF INTEGRATING GREEN ACCOUNTING ON PROFIT SUSTAINABILITY - Hardiningsih, Pancawati; Nasihin, Ihsan; Srimindarti, Ceacilia; Lisiantara, Gregorius Anggana (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
This research aims to evaluate the impact of integrating green accounting practices on sustainable profitability in corporations. Through an empirical analysis approach, this research examines how the implementation of green accounting can influence long-term profitability performance. The research population of companies registered on the IDX, especially the ASSRAT group that implements green accounting, is 40 companies. This research uses a stakeholder theory and legitimacy theory approach. The relationship between stakeholder theory and legitimacy theory provides a strong conceptual foundation to support the implementation of green accounting as a relevant and socially acceptable strategy. The research analysis technique uses multiple regression. by adding company scale control variables. The research results found that environmental disclosure and environmental performance have a significant positive effect on profit sustainability. These findings are proven to be able to provide insight into the importance of integrating green accounting by implementing PSAK 57 as the main driver for companies to integrate sustainable practices in their operations which in the end can have a positive impact on profit sustainability. The implications of these findings can help companies, regulators and other stakeholders to understand the positive impact of environmental responsibility in maintaining profits in the long term.